Increased intracranial pressure in a case of spinal cervical glioblastoma multiforme: analysis of these two rare conditions - C.M. de Castro-Costa; R.W.B. de Araújo; M.A. de Arruda; P.M. de Araújo; E.G. de Figueiredo (Arquivos de Neuro-Psiquiatria)
The authors describe a rare case of increased intracranial hypertension consequent to a spinal cervical glioblastoma multiforme in a young patient. They analyse the physiopathology of intracranial hypertension in spinal tumors and the rarity of such kind of tumor in this location, and its clinico-pathological aspects.